Exposure of adult zebrafish (Danio rerio) to Tetrabromobisphenol A causes neurotoxicity in larval offspring, an adverse transgenerational effect - Yu, Yunjiang; Hou, Yunbo; Dang, Yao; Zhu, Xiaohui; Li, Zhenchi; Chen, Haibo; Xiang, Mingdeng; Li, Zongrui; Hu, Guocheng (Journal of hazardous materials, 2021)
Tetrabromobisphenol A (TBBPA) is one of the most extensively used brominated flame retardants and is universally detected in the environment. However, information related to its transgenerational toxicity is sparse. Using zebrafish as a study model, adult fish were exposed to TBBPA at different concentrations (0, 3, 30, or 300 μg/L) for 42 d and then, the exposed adults were spawned in TBBPA-free water. The neurobehavior of adults and larval offspring was evaluated, and the levels of thyroxine (T4), triiodothyronine (T3) and neurotransmitters (acetylcholine, dopamine and gamma-aminobutyric acid) were quantified in larvae and embryos. Our results showed that TBBPA was detected in embryo and the locomotor activity of larval offspring was significantly reduced, suggesting that TBBPA can transfer to offspring and result in neurotoxicity in larval offspring. Furthermore, a reduction in T3 levels was observed in both the larvae and embryos. We also found a significantly decreased content of dopamine in larval offspring, accompanied by downregulated mRNA expression of rdr2b and drd3. Our results demonstrated that TBBPA can be transferred to offspring embryos, and subsequently induce neurotoxicity in larval offspring by affecting the amount of T3 transferred from the parents to embryos and the production of dopamine in larvae. [Display omitted] •Exposure of adult zebrafish to TBBPA results in neurotoxicity of larval offspring.•TBBPA can accumulate in the ovary and testis and be transferred to offspring embryos.•A reduction in T3 levels was observed in larvae and embryos originating from exposure of adult zebrafish to TBBPA.•The disruption of dopamine production and mRNA expression of dopamine receptors were observed in larvae.